Grounds for judicial decisions, consequentialism and pandemics (Research, Society and Development, 2021)
This study seeks to address the duty of reasoning in court decisions in its broad sense (motivation and justification), such as access to the Democratic Rule of Law and legal security, as well as addressing consequentialism, as it has been treated in Brazilian law and the dangers of reasons based on moral arguments. It is noteworthy that every reasoning should analyse the social bias and how the decision will affect society as a whole. For this, it will list the objectives of these institutes in procedural law from the perspective of a contemporary and constantly changing society. It is noteworthy that with the Covid-19 pandemic that devastates the country, this issue has gained more space, considering that there was an increase in decisions based on moral arguments that aim to decide in favor of collective well-being. Therefore, it lists which negative and positive results a consequentialist decision has implications for society.  The present work, the deductive methodology was chosen, with bibliographical research on doctrines, infra-constitutional and constitutional legislation, in addition to analysing the decisions of the Courts.